Ghost squad - Ortega, Claribel A. (Scholastic Press, 2020)
"For Lucely Luna, ghosts are more than just the family business. Shortly before Halloween, Lucely and her best friend, Syd, cast a spell that accidentally awakens malicious spirits, wreaking havoc throughout St. Augustine. Together, they must join forces with Syd's witch grandmother, Babette, and her tubby tabby, Chunk, to fight the haunting head-on and reverse the curse to save the town and Lucely's firefly spirits before it's too late."--Jacket flap.